„Światowid ” ze Zbrucza – kontrowersyjny symbol pogańskiej Słowiańszczyzny - Łuczyński, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2015)
The article is dedicated to the analysis and semantic interpretation of a monument referred to as the Zbruch Idol, discovered in 1848 near Liczkowce in the Ukraine. The author offers arguments in favour of the thesis that the artefact is a quadruple female made of stone by the Cumans in the late 13th/ early 14th century, and that the idol is a synthesis of the Turkish sepulchral sculpture.